Dumper deaths – public health breakdown on Karachi’s roads - Ali Shaikh, Masood; Syed Muhammad, Mubeen (Journal of the Pakistan Medical Association, 2025)
Dear Madam, In the past half a year, several newspaperreports have been published on deaths and injuries inchildren and adults resulting from the collision of adumper with other vehicles on the roads of Karachi1-5.Devastating families and upending lives and livelihoods,and adding to the burgeoning avoidable burden ofinjuries, with resultant strain on trauma care services inthe city. A dumper, also called a dumper truck, is a heavy, usually4-wheeled vehicle used on construction sites, miningoperations, infrastructure project sites, or for ferryingmunicipal garbage or debris collection. Often in theaftermath of these tragic road traffic accidents, outragedmobs retaliate by beating up culprit dumper drivers andtorching their vehicles1-3. The frequency and magnitudeof these avoidable road traffic accidents can no longer bedeemed and dismissed as isolated incidents, but reflect adeeper system failure and deteriorating trust in them. Continued...